Youth and videogames: perceptions about its informative treatment in the media - Estanyol, Elisenda; Montaña, Mireia; Planells, Antonio José (Estudios sobre el Mensaje Periodístico, 2019)
Videogames have become a powerful industry with more than 50 years of implantation in our society, being young people the most who participate in the digital game. This research analyses the opinions that the youth have about videogames, specifically Spanish individuals between 16 and 35 years, focusing on their perception of the information treatment in the media. This pioneering study in Spain, has been based on a survey with a sample of 1,000 young people living in this country. The study was carried out from the 20th to the 31st of May in 2017. The results highlight that the perception among young people of the informative treatment of videogames is different from the one they themselves have about the effects of the digital game, highlighting that, in their opinion, the media offer a more negative image.